2022
DOI: 10.22492/ije.10.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Facebook as a Flexible Ubiquitous Learning Space for Developing Speaking Skills

Abstract: he research studied the effectiveness of the integration of Facebook as a flexible ubiquitous learning space into the educational process for speaking skills development of undergraduate students learning English as a second language. For this purpose teaching was organised via a specially created and moderated Facebook group where various media resources, uploaded materials, links to different applications and other social networking opportunities were accumulated. It was designed to achieve the educational p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…Researchers tend to apply social media in language learning, especially foreign languages [13], [15], [16], [21], [22], [26], and second languages [2], [14], [23], [24]. This result shows that learning a foreign language and then a second language is the researchers' focus in using social media.…”
Section: B Target Languagementioning
confidence: 92%
See 2 more Smart Citations
“…Researchers tend to apply social media in language learning, especially foreign languages [13], [15], [16], [21], [22], [26], and second languages [2], [14], [23], [24]. This result shows that learning a foreign language and then a second language is the researchers' focus in using social media.…”
Section: B Target Languagementioning
confidence: 92%
“…However, this descriptive research needs to be strengthened by empirical intervention research to prove the concrete benefits of social media in second language learning. In this regard, empirical intervention studies found that the dominant social media platforms used were Facebook, WhatsApp, and Youtube [2], [15]- [20]. This result shows that those three platforms are popular in virtual communication in the community and are also widely used in language learning.…”
Section: A Social Media Platform For Language Learningmentioning
confidence: 96%
See 1 more Smart Citation
“…The skills or competencies required may be generic or specific. On the one hand, to face the challenges demanded by a changing and uncertain world, students need to develop generic competencies during their studies (Mykytiuk et al, 2022). On the other hand, today's companies require a workforce with specific competencies to perform increased complexity tasks (Marchi et al, 2019).…”
Section: / 17mentioning
confidence: 99%
“…The second one describes lockdown experience. The teaching and learning experience in some countries as Ukraine [22], Turkey [3], Ecuador [8], Nigeria [17], [25], [36], Philippines [24], Colombia [34], India [11], Thailand [38], Vietnam [26] and the United Arab Emirates [13], Mexico [2] is shown. Nevertheless, there are some gaps need to be filled in order to solve the hottest teaching and learning problems.…”
mentioning
confidence: 99%